Regulation of BECN1-mediated autophagy by HSPB6: Insights from a human HSPB6S10F mutant. Issue 1 (2nd January 2018) - Liu, Guan-Sheng; Zhu, Hongyan; Cai, Wen-Feng; Wang, Xiaohong; Jiang, Min; Essandoh, Kobina; Vafiadaki, Elizabeth; Haghighi, Kobra; Lam, Chi Keung; Gardner, George; Adly, George; Nicolaou, Persoulla; et al.
ABSTRACT: HSPB6/Hsp20 (heat shock protein family B [small] member 6) has emerged as a novel cardioprotector against stress-induced injury. We identified a human mutant of HSPB6 (HSPB6 S10F ) exclusively present in dilated cardiomyopathy (DCM) patients. Cardiac expression of this mutant in mouse hearts resulted in remodeling and dysfunction, which progressed to heart failure and early death. These detrimental effects were associated with reduced interaction of mutant HSPB6 S10F with BECN1/Beclin 1, leading to BECN1 ubiquitination and its proteosomal degradation. As a result, autophagy flux was substantially inhibited and apoptosis was increased in HSPB6 S10F -mutant hearts. In contrast, overexpression of wild-type HSPB6 (HSPB6 WT) not only increased BECN1 levels, but also competitively suppressed binding of BECN1 to BCL2, resulting in stimulated autophagy. Indeed, preinhibition of autophagy attenuated the cardioprotective effects of HSPB6 WT. Taken together, these findings reveal a new regulatory mechanism of HSPB6 in cell survival through its interaction with BECN1. Furthermore, Ser10 appears to be crucial for the protective effects of HSPB6 and transversion of this amino acid to Phe contributes to cardiomyopathy.